2010
DOI: 10.1089/fpd.2010.0547
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Prevalence of Asymptomatic Norovirus Infection in Korean Children

Abstract: The prevalence of asymptomatic norovirus (NoV) infection was investigated in children registered for kindergarten in Korea during the winter and summer. Children with no gastrointestinal symptoms, including diarrhea and abdominal pain, during the 2 weeks before and following sample collection were included in this investigation. NoV presence and genetic identification were determined with real-time reverse transcriptase-polymerase chain reaction and conventional nested reverse transcriptase-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…In the present study, a NoV prevalence of 29.6% was detected among healthy children in Cameroon. This is comparable to previously reported NoV prevalences of 22-33% [Gallimore et al, 2004;Mattison et al, 2010] but considerably higher than what was reported from presumably healthy Korean and English children of similar age group [Amar et al, 2007;Cheon et al, 2010;Phillips et al, 2010a]. A similarly high prevalence was found for EV and AdV while the rate of RoV infection was lower.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, a NoV prevalence of 29.6% was detected among healthy children in Cameroon. This is comparable to previously reported NoV prevalences of 22-33% [Gallimore et al, 2004;Mattison et al, 2010] but considerably higher than what was reported from presumably healthy Korean and English children of similar age group [Amar et al, 2007;Cheon et al, 2010;Phillips et al, 2010a]. A similarly high prevalence was found for EV and AdV while the rate of RoV infection was lower.…”
Section: Discussionsupporting
confidence: 83%
“…There is no clear animal reservoir for HuNoV, suggesting that it has other adaptations for viral maintenance between outbreaks. Asymptomatic and persistent shedding is likely to be one way that HuNoVs are maintained (4)(5)(6)(7)11), yet many questions remain about the mechanism of NoV persistence. Furthermore, while asymptomatic shedding has been demonstrated for many enteric viruses (43)(44)(45), a tractable model has not been established in which to study enteric persistence.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for an animal reservoir of HuNoV, suggesting that asymptomatic shedding within the human population initiates symptomatic infection. Indeed, PCR-based detection has shown that HuNoVs are present in asymptomatic individuals within a variety of communities and ranges in prevalence from 3 to 13% (4)(5)(6)(7). Furthermore, experimental infection of volunteers revealed that some individuals continue to shed virus for up to weeks after the resolution of symptoms (8), and there are examples where outbreaks likely originated with asymptomatic HuNoV shedders (9)(10)(11).…”
mentioning
confidence: 99%
“…NoV was identified using real-time RT-PCR and conventional nested RT-PCR (15). Briefly, a 50-l reaction mixture contained 5 l of viral RNA, 1 l (5 U) of reverse transcriptase, 25 l of TaqMan universal RT-PCR master mix (Applied Biosystems), a 400 nM concentration of each primer, 10 pmol of RING1(a), and either 5 pmol of RING1(b) probe for NoV GI detection or 5 pmol of RING2 probe for NoV GII.…”
mentioning
confidence: 99%
“…In each experiment, an NoV GI-or GII-specific standard curve was generated by a 10-fold serial dilution (10 7 to 10 1 copies) of purified NoV GI or GII RNA standards synthesized by in vitro transcription. NoV genotype was determined by RT-PCR and seminested PCR as previously described (15). All PCR products were sequenced using an ABI Prism 3100 automatic sequencer and BigDye Terminator cycle sequencing mix (Invitrogen, Carlsbad, CA).…”
mentioning
confidence: 99%